La scolarisation en maternelle : une analyse du récit et des dessins d'enfant - Maria Renata Prado-Martin (Presses universitaires de la Méditerranée, 2018)
This article is based on the doctoral research "Children in preschool : between resisting and submitting to the educational social project" (2008). The aim of this paper is to establish how children in preschool discover, assimilate and (re)interpret social norms through the assessment of the interviews and drawings of 26 daycare and kindergarten children. Their drawings having served as a basis for interview discussions, this article will focus on analyzing the content of discussions about the drawn images. An ethnographic approach was used for the fieldwork and interview assessment was carried out in light of concepts drawn from children's sociology and clinical sociology.